Preoperative molecular testing in thyroid nodules with Bethesda VI cytology: Clinical experience and review of the literature. Issue 4 (14th October 2020) - Labourier, Emmanuel; Fahey, Thomas J.
Abstract: Risk assessment is critical to determine the timing of elective surgeries and preserve valuable resources in time of pandemic. This study was undertaken to better understand the potential value of molecular testing to risk‐stratify thyroid nodules with malignant cytology (Bethesda VI). Systematic review of the literature contributed 21 studies representing 2036 preoperative specimens. The BRAF p.V600E substitution was detected in 46% to 90% of cases with a pooled positivity rate of 70% (95% confidence intervals: 64%‐76%). None of the studies used comprehensive oncogene panels. Retrospective analysis of 531 clinical specimens evaluated with the next‐generation sequencing ThyGeNEXT Thyroid Oncogene Panel identified a total of 436 gene alterations. BRAF mutation rate was 64% in specimens tested as part of standard clinical care and 75% in specimens from cross‐sectional research studies ( P = .022). Testing for additional actionable gene alterations such as TERT promoter mutations or RET and NTRK gene rearrangements further increased the diagnostic yield to 78%‐85% and up to 95% when including the ThyraMIR Thyroid miRNA Classifier. These data support the role of molecular cytopathology in surgical and therapeutic decision‐making and warrant additional studies.